Behaviour of the contact trace in a cam-follower system when the displacement law has been designed using bézier curves (2018)
The study shows the distribution of the contact trace in a cam - follower mechanism in which the Bézier curves of degrees 5, 7 and 9 have been used for the design of displacement of the follower. The equations that describe the movement of the follower and its derivatives are presented, the expressions are formulated for the contact trace, the force exerted on the mechanical assembly are formulated and the results obtained are presented in a model mechanism.